Srovnání výskytu pozitivní a negativní cévní remodelace u nemocných se stabilní vs. nestabilní anginou pectoris - Kovárník, T; Reznícek, V; Novácková, K; Linhart, A; Bĕlohlávek, J; Holm, F; Horák, J; Aschermann, M (Vnitrni lekarstvi, 2003)
BACKGROUND: The vascular remodelling refers to the increase or decrease in EEM (external elastica membrane) area that occurs during development of atherosclerosis. The positive remodeling, which was thought only as a compensatory factor during atheroma development, was also found as a one of the main features of unstable plaque. The intravascular ultrasound is very good tool to measure different type of arterial remodelling. These findings correlate with histologic post-mortem specimen with excellent results. AIM OF THE STUDY: To correlate the remodelling index from patients suffered from stable angina pectoris (SAP) and from patients suffered from unstable angina (UA). METHOD: We performed IVUS in 51 patients. In the group of patients with unstable angina were included patients with worsening angina symptoms in last six weeks or with angina in rest. We used IVUS--endosonics In-Vision with 30 MHz probe Awanar with mechanical pull-back. We studied the occurrence of positive remodelling, negative remodeling (an index that describes remodeling is expressed as: lesion EEM CSA/reference EEM CSA. If the lesion EEM area is greater than the reference EEM area, positive remodelling has occurred, and the index will be > 1.0. If the lesion EEM area is smaller than the reference EEM area, negative remodelling has occurred, and the index will be < 1.0). RESULTS: We performed the intravascular ultrasound in 51 patients, 22 patients (43.1%) with unstable angina (UA) and in 29 patients (56.9%) stable angina (SAP). The positive remodelling was found in 14 patients (63.6%) in UA group vs. 5 patients (17.2%) in group with SAP, p < 0.05. The negative remodelling was found in 6 patients (27.3%) in UA group vs. 23 patients (79.3%) in SAP group, p < 0.05. CONCLUSION: Positive remodelling is more often found in patients with UA vs. in patients with SAP. Positive arterial remodelling is therefore one of the features of unstable atherosclerotic plaque.
Keywords: nestabilní angina pectoris; mužské pohlaví; Coronary Vessels; lidé; Ultrasonography, Interventional; Male; Middle Aged; ženské pohlaví; lidé středního věku; koronární cévy; Angina Pectoris; Female; Humans; intervenční ultrasonografie; Angina, Unstable; angina pectoris